Prevalence and pattern of lower limbs peripheral artery disease detected by Duplex ultrasonography in patients having coronary artery blockage - Bhaduri, J; Raisuddin, M; Sarmin, M; Sayeed, MZ; Islam, MN (TAJ: Journal of Teachers Association, 2018)
Introduction : Atherosclerosis is a systemic disease which may affect coronary arteries, carotid arteries and peripheral arteries. Patients having coronary artery disease may also have lower limb peripheral arteries involvement due to atherosclerosis. This study is to see the prevalence and pattern of lower limb arteries involvement in patients having CAD. Methods: Duplex ultrasonic evaluation of peripheral arteries were done in 210 patients of CAD. Ultrasonic evaluation was done by B Mode image and on the basic of haemodynamic change. Result : Mean age of respondents was was 51.3 ± 10.4 years. 90% patient did not show any clinical sign or symptoms of PAD. 5.2% of patient has critical level of stenosis in one or multiple segments of lower limb arteries, 0.5 % patients had stenosis below the critical level. All the patients suffering from PAD were male patients. No statistical significant relation was found between occurrence of PAD and severity of CAD. Conclusion : Patient of CAD may have hidden PAD without any clinical presentation. Duplex ultrasonography can be a non invasive initial study to rule out the possibility of lower limb arterial insufficiency. TAJ 2016; 29(2): 62-65